If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 2e + 6 Reorder the terms: 0 = 6 + 2e Solving 0 = 6 + 2e Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-2e' to each side of the equation. 0 + -2e = 6 + 2e + -2e Remove the zero: -2e = 6 + 2e + -2e Combine like terms: 2e + -2e = 0 -2e = 6 + 0 -2e = 6 Divide each side by '-2'. e = -3 Simplifying e = -3
| 8/5x4 | | 72x/36x | | 2cos(10x)-1=0 | | 70=-5(3a-5) | | 2(90)-8(30)=180 | | .5m+6.4=4.9-1m | | -61=-2(4n+4)-5 | | 6(n-4)=2(n+12) | | 9(4x-3)=45 | | -3(1-5x)=72 | | 12X+9=7X+21 | | f(x)=x^5+7x^4-3x^3+2x+1 | | 2+6(-3k+1)=116 | | 6(w-4)=3(w+9) | | 5m-3=27-2m | | 2(90)+-8(30)=180 | | 7z+2=9-32 | | 3(4+6x)-4x=-72 | | 5/7x4= | | 3x=x/14 | | f(25)=0.01*2 | | 1/3(15m-9)=27-2m | | 0.09xX=135.45 | | 2(u+4)=-10 | | 15+6a=16 | | 6(1+3b)=78 | | 90+4y=x | | 6n-4=5n+11 | | 3(-6+4m)=-90 | | 5c^2+5c-60= | | -8y+2x=180 | | 84=-6(2k-2) |